SOSIALISASI UPAYA PENCEGAHAN PERNIKAHAN DINI BERBASIS ISLAM PADA PELAJAR SMAN 2 MATARAM - Agus Kurnia; Agil Zakita Wardhati; Annisa Dwi Setyaningrum; Syariah Pantasari; Dony Mulawarman; Lalu Rahmat Iqbal; Virza Fahlyfi ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2025)
Early marriage is a significant social issue in Indonesia, especially in West Nusa Tenggara (NTB), with the rate of child marriage reaching 15.485% in 2018. This phenomenon has a negative impact on children's health, education, and welfare. This research aims to provide socialization and education about Islamic-based early marriage prevention to SMAN 2 Mataram students, to increase their awareness. The methods used include the delivery of interactive materials, discussions, and evaluations through pre-test and post-test. The results of the activity showed an increase in students' understanding of the negative impacts of early marriage, with post-tests demonstrating their commitment to supporting the prevention of the practice. In conclusion, this socialization succeeded in providing an in-depth understanding of the importance of postponing marriage for health and education. This educational activity is significant in creating a young generation who cares about the issue of early marriage, so that students can become agents of change that bring a positive influence on society and support children's rights to education and a better future.